Negotiating Religious Differences: The Strategies of Interfaith Chaplains in Healthcare - Cadge, Wendy; Sigalow, Emily (Journal for the scientific study of religion, 2013)
Chaplains in healthcare increasingly work in interfaith roles with patients and families from a range of religious and spiritual backgrounds. Some move with ease between their own religious backgrounds and those of the individuals with whom they work. Others encounter tensions as their status as a person of faith comes into conflict with their status as an interfaith chaplain. We explore the two main strategies—neutralizing and code-switching—chaplains at one large academic medical center use when working with patients and families whose religious and spiritual backgrounds are different from their own. Through training in clinical pastoral education and experiences on the job, chaplains learn to neutralize (use a broad language of spirituality that emphasizes commonalities rather than differences) and to code-switch (use the languages, rituals, and practices of the people with whom they work). To the extent that the strategies evident here are present among chaplains in a broader range of institutional settings, they suggest a kind of spiritual secularism or broad approach to meaning makings that may be facilitated by interfaith chaplains in a range of settings.